2018
DOI: 10.1371/journal.pone.0192063
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of linkage disequilibrium and analysis of genetic diversity in Korean chicken lines

Abstract: The development of genetic markers for animal breeding is an effective strategy to reduce the time and cost required to improve economically important traits. To implement genomic selection in the multibreed chicken population of Korea, an understanding of the linkage disequilibrium (LD) status of the target population is essential. In this study, we performed population genetic analyses to investigate LD decay, the effective population size, and breed diversity using 600K high-density single nucleotide polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
(45 reference statements)
2
24
0
Order By: Relevance
“…Several studies, using DNA fingerprinting, polymorphic microsatellite markers, and 600k SNP chip data, found evidence of such genetic introgressions into the KNC since 1960. Based on the previous results, KNC lines are closely related to Cornish, New Hampshire, and RIR breeds and genetically more distant from the white Leghorn breed ( Lee et al., 1996a , b ; Kong et al., 2006 ; Oh et al., 2008 ; Suh et al., 2014 ; Seo et al., 2017 ; Seo et al., 2018 ). Seo et al.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Several studies, using DNA fingerprinting, polymorphic microsatellite markers, and 600k SNP chip data, found evidence of such genetic introgressions into the KNC since 1960. Based on the previous results, KNC lines are closely related to Cornish, New Hampshire, and RIR breeds and genetically more distant from the white Leghorn breed ( Lee et al., 1996a , b ; Kong et al., 2006 ; Oh et al., 2008 ; Suh et al., 2014 ; Seo et al., 2017 ; Seo et al., 2018 ). Seo et al.…”
Section: Resultsmentioning
confidence: 91%
“…Sharing of the novel BSNP haplotypes across the KNC lines is in agreement with previous studies that found KNC lines have a close genetic relationship by sharing common ancestors at the origin ( Seo et al., 2013 ; Shu et al., 2014 ; Choi et al., 2015 ). In the early backyard breeding system, the KNC lines may have interbred despite being separated based on the feather color and body conformation traits ( Seo et al., 2013 , 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, Indicine breeds have a lower LD than Taurine, suggestive of a larger ancestral population (e.g., Porto-Neto et al, 2014). The involvement of human in shaping genetic makeup of livestock is also evident in domestic chickens, where local breeds mostly exhibit shorter extent of LD (Khanyile et al, 2015) and among the commercials, the broilers presents faster decay of LD than layer populations (Pengelly et al, 2016;Seo et al, 2018 andHérault et al, 2018). This is attributed to a more intensive selection scheme running over many generations during past several decades in layers resulting in a lower population haplotype diversity and a smaller Ne.…”
Section: To What Extent Is Ld In Farm Animals Influenced By Humans?mentioning
confidence: 99%